Transition of dominant canine parvovirus genotype from 2b to 2c in Vietnamese dogs - Nguyen Van, Dung; Le, Thanh Dinh Ha; Maeda, Ken (Veterinaria italiana, 2022)
Canine parvovirus (CPV) is one of the most important pathogens causing enteritis in dogs. Although there have been a few reports of CPV in Vietnam, recent information on CPV infection in domestic dogs in Vietnam is limited. Faecal samples collected from 30 diarrheic and 50 healthy dogs were examined by PCR for detection of CPV DNA. The prevalence of CPV in diarrheic dogs (43.3%, 13/30) was significantly higher than in healthy dogs (4.0%, 2/50), indicating that CPV was a major cause of diarrhoea in domestic dogs. Genotyping of 15 CPV strains showed that both CPV‑2a and CPV‑2c were circulating and that CPV‑2c was a dominant CPV variant in Vietnam. Virus isolation was performed from faecal samples using A72/cSLAM cells, and nine CPV strains were successfully isolated. The dominant genotype spreading among Vietnamese dogs has changed from CPV‑2b to CPV‑2c.